Synthesis and Studies of Molecules Exhibiting Excited State Proton Transfer and Aggregation Induced Emission as Sensors and Logic Devices - Gupta, Akul Sen (My University, 2017)
The research investigations in the present thesis revealed that the presence of electron donating and withdrawing groups like containing bromo, diethyl amino, formyl on the hydroxyary-benzimidazoles/substituted benzimidazoles highly affect sensing ability of the molecules. It has been clearly predicted that on changing the substituent from electron donating to electron withdrawing group, analyte to be detected could be tuned. Furthermore, incorporations of ESIPT and AIE moieties onto single platform showed the wide range emission from 400-800 nm. Self-quenching effect at higher concentration of molecules could be eradicated upon incorporation of ESIPT and AIE moieties onto single platform. Importantly, large Stokes shift could be achieved with higher emission intensity in polar solvents. ESIPT-AIE molecules have high quantum yields because of their unique propeller-like structure therefore intramolecular rotations are restricted in aggregated state, which prohibits energy dissipation via non-radiative channels in the presence of different analyte. The synthesis of dyad combinations has led to miniaturization of different logic devices like sequential XNOR logic gate, 2-1 encoder, 1-2 decoder and 4-2 bit encoder which has the futuristic applications in digital data-processing functions in conventional electronic industry. ESIPT–AIE coupled phenomenon can be exploited for designing sensors with large signal to noise rations (SNRs) or big pseudo-Stokes shifts; could be used to engineer sensors for monitoring multiple analytes. With their unique merits, it is believe that dual and multiple mechanism-based fluorescent sensors will be employed for unprecedented and exciting applications in diverse fields, especially in high SNR fluorescence bio-imaging, investigating interactions of multiple biological species, OLEDs, and developing optical logical devices with multiple inputs and outputs.
Keywords: Chemosensors; Benzimidazole; Schiff Base; AIE; ESIPT; Tetraphenylethylene; Logic Gates